Techno-Economic Feasibility Study of Hydrogen Transportation in Greenland Using Pipeline and Maritime Routes - Hauwa Bappah Dukku; Javier Arnaut; Cameron Johnstone; Annalisa Riccardi; Stephanie Ordonez Sanchez (한국해양공학회지, 2025)
Greenland's abundant renewable energy resources position it as a potential producer of green hydrogen, a promising energy carrier for global decarbonization efforts. This research aims to evaluate the economic feasibility of hydrogen transportation in Greenland, focusing on compressed gas via pipelines and liquefied hydrogen via maritime routes. The study employs a comprehensive methodology that includes economic analysis of production, liquefaction, and transportation costs. This approach integrates a wide range of methods available in the literature and considers various components of the hydrogen supply chain, going beyond the typical focus on transportation strategies alone. Results indicate that pipelines are more cost-effective for shorter distances (<1,500 km) and higher demand, whereas shipping is better suited for longer distances and larger volumes. A case study of transporting hydrogen from Paamuit to Nuuk revealed that for a production capacity of 40 t/d, the cost of pipeline transport was 1.3 USD/kg, whereas for shipping it was 2.7 USD/kg. These findings contribute significantly to the development of a hydrogen economy and highlight Greenland's potential as a competitive player in the global green hydrogen market. The research provides valuable insights for decision-makers in planning efficient and economical hydrogen transportation strategies.